2022
DOI: 10.3389/fnins.2021.824759
|View full text |Cite
|
Sign up to set email alerts
|

An Impending Paradigm Shift in Motor Imagery Based Brain-Computer Interfaces

Abstract: The development of reliable assistive devices for patients that suffer from motor impairments following central nervous system lesions remains a major challenge in the field of non-invasive Brain-Computer Interfaces (BCIs). These approaches are predominated by electroencephalography and rely on advanced signal processing and machine learning methods to extract neural correlates of motor activity. However, despite tremendous and still ongoing efforts, their value as effective clinical tools remains limited. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…The vast majority of non-invasive brain-computer interfaces (BCIs) try to identify and characterize single imagined movements using temporally averaged power in the mu and beta bands (Brodu et al, 2011; Herman et al, 2008; Pfurtscheller & Neuper, 2001). Most recent advances in the field rely on sophisticated machine learning techniques (Barachant et al, 2012; Llera et al, 2014; Lotte et al, 2018; Song et al, 2013), but we have recently argued that what is needed for further predictive power is a more fine-grained approach to feature extraction aimed at the temporal signatures of bursts of mu and beta activity (Papadopoulos et al, 2022). We have here demonstrated that averaged beta power includes many burst motifs that do not change in rate pre-movement.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of non-invasive brain-computer interfaces (BCIs) try to identify and characterize single imagined movements using temporally averaged power in the mu and beta bands (Brodu et al, 2011; Herman et al, 2008; Pfurtscheller & Neuper, 2001). Most recent advances in the field rely on sophisticated machine learning techniques (Barachant et al, 2012; Llera et al, 2014; Lotte et al, 2018; Song et al, 2013), but we have recently argued that what is needed for further predictive power is a more fine-grained approach to feature extraction aimed at the temporal signatures of bursts of mu and beta activity (Papadopoulos et al, 2022). We have here demonstrated that averaged beta power includes many burst motifs that do not change in rate pre-movement.…”
Section: Discussionmentioning
confidence: 99%
“…However, there has recently been a considerable paradigm shift towards considering transient signal features on the single trial level (Chen et al, 2021;Coleman et al, 2024;Jones, 2016;Little et al, 2019;Lundqvist et al, 2024Lundqvist et al, , 2016Rayson et al, 2023;Shin et al, 2017;Torrecillos et al, 2018;Vigué-Guix and Soto-Faraco, 2022;Wessel, 2020). Therefore, considering that computational models describing the neuronal generators of specific burst waveform shapes (Bonaiuto et al, 2021;Sherman et al, 2016;Szul et al, 2023) offer an improved theoretical interpretability of the observed signal modulations, applications leveraging such signal characteristics, like beta bursts, could potentially benefit from incorporating recent neuroscience findings (Papadopoulos et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously argued that analyzing beta burst activity should enable us to gain access to classification features that are at least as sensitive as beta band power [88]. If this hypothesis is valid, then we should be able to test it and verify it using publicly available datasets.…”
Section: Introductionmentioning
confidence: 99%